Venous thromboembolism in pediatric patients with acute lymphoblastic leukemia under chemotherapy treatment. Risk factors and usefulness of thromboprophylaxis. Results of LAL‐SEHOP‐PETHEMA‐2013. (27th March 2022) - Ruiz‐Llobet, Anna; Gassiot, Susanna; Sarrate, Edurne; Zubicaray, Josune; Dapena, José Luis; Rives, Susana; Sevilla, Julián; Menárguez López, Ángela; Panesso Romero, Melissa; Montoya, Catalina; Vagace, José Manuel; Molina Hurtado, José Ramón; et al.
Abstract: Introduction: Symptomatic venous thromboembolism (VTE) is diagnosed in 3%–14% of patients during pediatric acute lymphoblastic leukemia (ALL) therapy. There are well‐known risk factors, but the role of others as inherited thrombophilia is still controversial. Prophylaxis with low molecular weight heparin (LMWH) has been described, but its use is not globally accepted. Methods: A retrospective multicentric study in ALL patients 1–18 years old following SEHOP‐PETHEMA‐2013 treatment guideline was performed to evaluate VTE rate, anticoagulant treatment, outcome, risk factors, and safety and usefulness of LMWH administration as primary thromboprophylaxis in children with inherited thrombophilia. Results: A total of 652 patients were included in the study. VTE incidence was 8.7%. Most of the cases occurred during induction therapy associated with central venous catheter. Univariant analysis showed that family history of thrombosis, presence of mediastinal mass, high‐risk treatment group, and inherited thrombophilia were statistically significant risk factors. LMWH administration seemed to decrease VTE rate in patients with inherited thrombophilia and those with T‐cell ALL phenotype. Conclusion: Most of the VTE cases occurred in patients without inherited thrombophilia, but when it is present, the VTE risk is higher. LMWH administration was useful to decrease VTE in these patients.